2019
DOI: 10.1186/s13023-019-1066-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect and safety of treatment with ACE-inhibitor Enalapril and β-blocker metoprolol on the onset of left ventricular dysfunction in Duchenne muscular dystrophy - a randomized, double-blind, placebo-controlled trial

Abstract: Background X-linked Duchenne muscular dystrophy (DMD), the most frequent human hereditary skeletal muscle myopathy, inevitably leads to progressive dilated cardiomyopathy. We assessed the effect and safety of a combined treatment with the ACE-inhibitor enalapril and the β-blocker metoprolol in a German cohort of infantile and juvenile DMD patients with preserved left ventricular function. Methods Trial design Sixteen weeks single-arm open run-in therapy with enalapril a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…In the first of those trials, Duboc et al 9 found no difference in LVEF in the subjects treated with perindopril for 3 years when compared with subjects receiving placebo. In the second trial, 20 19 months of combination therapy with enalapril and metoprolol did not alter the time it took for LV FS to fall to a level below 28% when compared with controls. In the third study, 16 2 years of treatment with enalapril appeared to reduce the progression of fibrosis as assessed by CMR and late gadolinium enhancement when compared with a placebo group; however, there was no significant difference in LVEF between the two groups.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In the first of those trials, Duboc et al 9 found no difference in LVEF in the subjects treated with perindopril for 3 years when compared with subjects receiving placebo. In the second trial, 20 19 months of combination therapy with enalapril and metoprolol did not alter the time it took for LV FS to fall to a level below 28% when compared with controls. In the third study, 16 2 years of treatment with enalapril appeared to reduce the progression of fibrosis as assessed by CMR and late gadolinium enhancement when compared with a placebo group; however, there was no significant difference in LVEF between the two groups.…”
Section: Resultsmentioning
confidence: 85%
“…Randomized trials ( n = 10) studied the effects of ACEI or ACEI plus BB ( n = 4), 8,9,16,20 aldosterone inhibitors ( n = 2), 29‐31 and four other novel therapies 26‐28,32 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-eight patients from 10 sites were centrally randomized into the intervention group (combined treatment with enalapril and metoprolol) and a placebo control group. The results showed that the administration of ACEI and β-blocker delayed the progression of intrinsic cardiomyopathy to left ventricular failure in DMD patients with preserved left ventricular function, although this did not reach statistical significance[25]. Further studies should be conducted to determine the effect of ARNIs in DMD patients with preserved left ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…While there was no difference in left ventricular ejection fraction between groups, this may have been a function of the duration and size of the study. Longer term and larger studies will be needed to answer this question more definitively given the relatively slow progression of dysfunction noted in the current era 34,35 . Based on the current data, the Care Considerations have recommended initiating therapy at age 10, 1 while the AHA has suggested this approach may be considered before the onset of reduced systolic function 18 .…”
Section: Angiotensin‐converting Enzyme Inhibitors and Angiotensin II mentioning
confidence: 99%